2007
DOI: 10.1366/000370207781393280
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Prediction Outlier Diagnostics in Determining a Successful Inter-Vendor Multivariate Calibration Model Transfer

Abstract: This paper reports on the transfer of calibration models between Fourier transform near-infrared (FT-NIR) instruments from four different manufacturers. The piecewise direct standardization (PDS) method is compared with the new hybrid calibration method known as prediction augmented classical least squares/partial least squares (PACLS/PLS). The success of a calibration transfer experiment is judged by prediction error and by the number of samples that are flagged as outliers that would not have been flagged as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…While not part of this paper, methods exist to determine oultiers 1,2 and indeed represent a critical aspect of calibration maintenance and transfer. 63 It has been shown that only a few samples are needed to update the model but these samples should be selected (if possible) based on a selection strategy that maximizes the ability of the standardization set to properly span the new conditions. With a standardization set properly spanning the new situation or secondary instrument, improved results should be obtainable compared to a random selection of samples for the standardization set.…”
Section: Resultsmentioning
confidence: 99%
“…While not part of this paper, methods exist to determine oultiers 1,2 and indeed represent a critical aspect of calibration maintenance and transfer. 63 It has been shown that only a few samples are needed to update the model but these samples should be selected (if possible) based on a selection strategy that maximizes the ability of the standardization set to properly span the new conditions. With a standardization set properly spanning the new situation or secondary instrument, improved results should be obtainable compared to a random selection of samples for the standardization set.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the standardization set should be representative of the new condition. However, the actual method used to select a standardization sample subset can affect the calibration transfer quality and, hence, prediction in the new conditions [11,37]. For example, the transformation quality of the piecewise direct standardization (PDS) algorithm was found to be sensitive to the method of subset selection, while prediction augmented classical least squares/partial least squares (PACLS/ PLS) was not [37].…”
Section: Standardization Samplesmentioning
confidence: 99%
“…However, the actual method used to select a standardization sample subset can affect the calibration transfer quality and, hence, prediction in the new conditions [11,37]. For example, the transformation quality of the piecewise direct standardization (PDS) algorithm was found to be sensitive to the method of subset selection, while prediction augmented classical least squares/partial least squares (PACLS/ PLS) was not [37]. It may be that a consensus (bagging, ensemble, fusion, stacking) model approach [38][39][40][41][42][43] would provide a better updated model compared to updating a model with one subset, i.e., multiple updated models are formed with different standardization sets and some form of composite prediction is reported from the models deemed acceptable.…”
Section: Standardization Samplesmentioning
confidence: 99%
“…These methods make use of hybrid classical least squares (CLS)/PLS methods to affect the transfer but do require samples in common. Dow was involved in the study of this technology and brought to light an often overlooked aspect of calibration transfer, preservation of outlier diagnostics . It was found that when using piecewise direct standardization for this particular application, the transferred models incorrectly identified many of the prediction samples as outliers while still providing reasonable predictions.…”
Section: Chemometrics Research At the Dow Chemical Companymentioning
confidence: 99%